A comparative pattern of lectin-binding in the endometrial glands of the uterus and placenta of healthy buffaloes and bovines at early gestation - Caspe, Sergio Gaston; Konrad, Jose Luis; Moore, Prando Dadin; Sala, Juan Manuel; Lischinsky, Lilian Haydee; Campero, Carlos Manuel; Barbeito, Claudio Gustavo (Tech Science Press, 2021)
Water buffalo (Bubalus bubalis) and domestic cattle (Bos taurus) are closely related species. However, embryo transfer interspecies has been attempted without any success. The failure in hybrid embryo-implantation is associated with the glycocode in the maternal-fetal interface. Glycosylation patterns have been studied in different species of ruminants; however, in B. bubalis, only the binucleated cells (BNC) have been analyzed. This glycocode is essential for a successful embryo-implantation and can be defined by Lectin-Histochemistry (LHC). The aim of this study is to compare the glycosylation pattern of placenta and uterus in water buffaloes and cattle by LHC. Tissue samples of placenta and uterus from pregnant Mediterranean female water buffaloes (Buf1) and Angus cows (Bov1) were analyzed. All animals were euthanized at 98 days of gestation. LHC was carried out using twelve lectins (Con A, LCA, PSA, sWGA, PHA-e, SBA, UEA-1, WGA, RCA-1, PNA, DBA, BSA-1). The intensity of lectin binding was semiquantitatively scored using a scale of 0 (negative) to 3 (strongly positive). Difference between species was found in trophoblast layer by PSA, SWGA, PNA and BSA-1, in BNC, and in the mononuclear cells by LCA, PSA, PHA-e, DBA, BSA-1, PNA. In utero, differences in the apical cellular membrane and the secretion of glands were identified by DBA and RCA-1, and in the cytoplasm of those glandular epithelial cells by PHA-e, BSA-1, WGA, and SBA. In both species, BNC presented a strong positive reaction with DBA and SBA, a moderate response by LCA, PHA-e, BSA-1 and PNA lectin, and a low reaction by PSA, UEA-1, SWGA, WGA, Con A and RCA-1. The results found in this study suggest that although both species are closely related, glycosylation patterns in the placenta and uterus are different, thus providing a possible reason for embryo transfer not being possible between these species.